2011
DOI: 10.5195/jwsr.2011.415
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking Corporate Directorates and the Global City Hierarchy

Abstract: This paper examines the direct and indirect economic linkages of the most prominent cities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…URL: http://ibis.geog. ubc.ca/~ewyly/g350/gawc.pdf (accessed 1.06.2020) -«эксклюзивное» -с применением оригинальных приёмов исследования городов, например, с позиций концепции цепочек добавленной стоимости, библиометрического анализа, «центральности в сети»; а также путём исследования расселения членов советов директоров ТНК (Carroll 2007;Derudder, WIltox 2010;Kentor et al 2011;Neal 2011).…”
Section: Mgimo Review Of International Relations • 13(3) • 2020unclassified
“…URL: http://ibis.geog. ubc.ca/~ewyly/g350/gawc.pdf (accessed 1.06.2020) -«эксклюзивное» -с применением оригинальных приёмов исследования городов, например, с позиций концепции цепочек добавленной стоимости, библиометрического анализа, «центральности в сети»; а также путём исследования расселения членов советов директоров ТНК (Carroll 2007;Derudder, WIltox 2010;Kentor et al 2011;Neal 2011).…”
Section: Mgimo Review Of International Relations • 13(3) • 2020unclassified
“…However, while the data based on passenger flows and corporations are widely acknowledged in this literature, there are several other promising approaches as well. For example, Carroll (2007; see also Kentor et al, 2011) estimates cities' relative global prominence on the basis of network analysis of interlocking directorates of top corporations. Others explored cities' relative positions in Internet backbone networks (Malecki, 2011;Tranos, 2011;Tranos et al, 2014;Vinciguerra et al, 2010), while Matthiessen et al (2010) analyzed the changing network of cities identified on the basis of scientific collaborations.…”
Section: Prior Research On Global Centralitymentioning
confidence: 99%
“…However, few non-Japanese financial firms use Tokyo as an Asia-Pacific headquarters. Although Japanese financial firms in Tokyo possess global ties, as a group they are relatively isolated from global corporate networks (Kentor et al, 2011). Tokyo has never been a network hub from which Chinese financial firms operated.…”
Section: The Structure Of Asian Financial Center Networkmentioning
confidence: 99%